Preparing Doctors in Training for Health Activist Roles: A Cross-Institutional Community Organizing Workshop for Incoming Medical Residents - Eleanor H. Emery; Jonathan D. Shaffer; Danny McCormick; Jessica Zeidman; Sophia R. Geffen; Predrag Stojicic; Marshall Ganz; Gaurab Basu (Association of American Medical Colleges, 2022)
Introduction Physicians are increasingly being called on to address inequities created by social and structural determinants of health, yet few receive training in specific leadership skills that allow them to do so effectively. Methods We developed a workshop to introduce incoming medical interns from all specialties at Boston-area residency programs to community organizing as a framework for effective physician advocacy. We utilized didactic sessions, video examples, and small-group practice led by trained coaches to familiarize participants with one community organizing leadership skill-public narrative-as a means of creating the relationships that underlie collective action. We offered this 3-hour, cross-institutional workshop just prior to intern orientation and evaluated it through a postworkshop survey. Results In June 2019, 51 residents from 13 programs at seven academic medical centers attended this workshop. In the postworkshop survey, participants agreed with positive evaluative statements about the workshop's value and impact on their knowledge, with a mean score on all items of over 4 (5-point Likert scale, 1 = strongly disagree, 5 = strongly agree; response rate: 34 of 51). Free-text comments emphasized the workshop's effectiveness in evoking positive feelings of solidarity, community, and professional identity. Discussion The workshop effectively introduced participants to community organizing and public narrative, allowed them to apply the principles of public narrative by developing their own stories of self, and demonstrated how these practices can be utilized in physician advocacy. The workshop also connected participants to their motivations for pursuing medicine and stimulated interest in more community organizing training.